RANCANG BANGUN INSTALASI PENGOLAHAN AIR LIMBAH RUMAH POTONG HEWAN (RPH) AYAM DENGAN PROSES BIOFILTER - Said, Nusa Idaman; Yudo, Satmoko (Jurnal Air Indonesia, 2006)
More than 90 % of Jakarta livestock supply, especially poultry, originated from outside the area. Meanwhile temporary places and slaughterhouse are spread out in some locations in Jakarta area, even most of them located in residences area. Almost all wastewater are not processed but straightly discharged to the sewer or river around the house. These spread chickens slaughterhouse activities caused environmental pollution which is difficult to control.This paper discussed about the design of wastewater process installation of chickens slaughter by biofilter anaerob-aerob process and test of its process result. Based on the test the removal efficiency of COD, Permanganate, BOD and Total Suspended Solid (TSS) were 86.52 %, 82.85 %, 88.79 % and 94.1 % respectively..Ã‚Â Keyword : Design, process, wastewater, chicken slaughterhouse, biofilter.